2003
DOI: 10.1046/j.0936-6768.2003.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Ovulation and Conception Rate in Primiparous and Multiparous Cows after Synchronization of Ovulation with GnRH and PGF

Abstract: Conception rates after Ovsynch have been higher in primiparous than in multiparous cows. The objective of this study was to investigate whether this difference might be due to differences in ovulation rate or follicular size. The experiment was conducted with 136 Holstein Frisian cows from a commercial herd in Brandenburg, Germany. All cows were synchronized using Buserelin (GnRH analogue) at day -10, Tiaprost (PGF2alpha analogue) at day -3 and again GnRH at day -1. Timed artificial insemination (TAI) was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
(27 reference statements)
2
9
2
3
Order By: Relevance
“…2003). The occurrence of oestrus early after PGF 2 α was more frequent in primiparous than in older cows (Tenhagen et al. 2003).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…2003). The occurrence of oestrus early after PGF 2 α was more frequent in primiparous than in older cows (Tenhagen et al. 2003).…”
Section: Discussionsupporting
confidence: 76%
“…The synchronization rate of the GPG protocol, defined as percentage of animals ovulating within 40 h after the second dose of GnRH was lower than in lactating dairy cows (Vasconcelos et al. 1999; Tenhagen et al. 2003) but higher than that reported for heifers by Pursley et al.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Relationship between the follicle size and P/AI at 31 days: a) estimated conception rate and b) real P/AI at 31 days. are known to produce more milk than primiparous cows, and increasing milk production, feed intake, and steroid metabolism could have potential effects on the increasing follicle size in multiparous cows (8,30). Heat stress during the warm season is accepted as a major cause of low fertility in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller follicles were also found to be related to high embryo survival (25). However, other studies showed that follicle size does not affect pregnancy in cows (8,(16)(17)(18). Thus, the objectives of this study were to detect to relationship between follicle size and P/AI and to determine the factors that affect follicle size at the time of AI in lactating dairy cows.…”
Section: Introductionmentioning
confidence: 99%